Seam - Faizullah, Tarfia (Crab Orchard award series in poetry., 2014)
The poems in this captivating collection weave beauty with violence, the personal with the historic as they recount the harrowing experiences of the two hundred thousand female victims of rape and torture at the hands of the Pakistani army during the 1971 Liberation War. As the child of Bangladeshi immigrants, the poet in turn explores her own losses, as well as the complexities of bearing witness to the atrocities these war heroines endured. Throughout the volume, the narrator endeavors to bridge generational and cultural gaps even as the victims recount the horror of grief and personal loss.